RETROSPECTIVE EFFICACY ANALYSIS OF ACUTE VASOREACTIVE TEST AS A CRITERIA FOR SURGERY IN CHILDREN WITH INBORN LEFT-TO-RIGHT BLOOD SHUNTING AND PULMONARY ARTERIAL HYPERTENSION - A. Mullen; G. Butrous; K. Abzaliev (Российский кардиологический журнал, 2018)
Aim. Retrospective analysis of efficacy of the acute vasoreactive test (AVRT) as a criteria for operability of children with inborn left-to-right blood shunting complicated by pulmonary arterial hypertension (IRLBS-PAH), by an experience of one center.Material and methods. Retrospective analysis of the data of right heart chambers catheterization and echocardiographic study from 29 case histories of BS-PAH patients during 2012-2016. Results of AVRT are interpreted by modified Barst criteria (decline of pulmonary vascular resistance index, PVRI, and relation of PVRI to the index of systemic vascular resistance, SVR more than 20%, and the and PVRI <6 Wood units/m2 in PVR/SVR <0,3). In accordance with the results of AVRT, patients were selected to two main groups: group 1 — children with positive response, group 2 — children with negative response. After correction of the inborn defect in bith groups, following assessment of cardiovascular system condition was done by echocardiographical study in one week and one month. Metrics of echocardiography data was indexed. For the defect of interventricular septum (DIVS), indexation of the size was done via the relation to aortic root diameter, that was measured in parasternal position, longitudinal axis. Systolic pressure in the right ventricle was measured by the velocity of tricuspid regurgitation, measured in apical four-chamber position. Mean values with the standard deviation and p-values were calculated in R studio 2017 software, v.1.0.153.Results. Among 29 patients, girls to boys relation was 4,8:1. Mean age 6,0±4,9 y. o. For group 1: median of DIVS 1,4 with the value of additional shunting 9,93±9,39 mm, baseline systolic pressure in the right ventricle (SPRV) 57,96±20,16 mmHg, in one month after surgery 38,96±14,16 mmHg. No complications registered. In the second group, median DIVS 0,4 with additional shunting 3,3±0 mm. Baseline SPRV 66,05±17,27 mmHg, with the decline in one month after transcatheter closure to 57,4±17,35 mmHg. During the early post-surgery period, in 2 patients of group 2 there was pulmonary crisis, treated with inhalatory iloprost. Conclusion. Acute vasoreactive test is effective criteria of operability assessment of inborn left-to-right blood shunting, complicated by pulmonary arterial hypertension, in pediatrics.